Magnetobreakdown oscillations of Nernst-Ettingshausen field in layered conductors - Galbova, O. (Condensed Matter Physics, 2016)
In the presented report, the Nernst-Ettingshausen effect in layered conductors is investigated. Considering a Fermi surface (FS) consisting of a slightly corrugated cylinder and two corrugated planes distributed periodically in the momentum space, the thermoelectric effects are considered under general assumptions for the value of a magnetic breakdown probability. As a result of an external generalized force, the FS sheets in layered conductors with a multisheet FS appear to be so close that the charge carriers (as a result of magnetic breakdown) can move from one FS sheet to another. In addition, the distribution functions of the charge carriers and the magnetic breakdown oscillations of thermoelectrical field along the normal to the layer, under different values and orientations of the magnetic field, B, are calculated. It is shown that if the magnetic field is deflected from the xz-plane at an angle ϕ, the oscillation part of a thermoelectrical field along the normal to the layer under condition sinϕtanϑ À 1 is mainly determined with the Nernst-Ettingshausen effect.